Developing a leadership framework for improving construction business organisation performance in South Africa - Alade, Kehinde Temitope (Department of Construction Economics and Management, 2022)
The South African construction industry is experiencing challenging times, like its counterparts globally, which has led to the failure of known large contractors. While some studies have suggested different reasons for this, a stream of scholars argued that company leadership contributes significantly to the organisation's performance. Studies on leadership in construction have mainly been undertaken at project level, considering that construction organisations are project-based. This study examined the leadership of construction organisations and whether the traits, skills, role, style and strategic decisions of company leaders impacted on the long-term performance and sustainability of contracting firms in South Africa. The main question investigated in this study is: what combination of leadership traits, skills, style, role, and strategic decisions results in superior and sustainable construction organisation performance, when moderated by strategic decisions of CEO/company leadership? The study draws from theoretical perspectives, namely the ‘upper echelons' theory, strategic leadership theory, and the Full Range Leadership Model (FRLM), to develop a conceptual framework. A convergent mixed-method research design was used to advance the investigation. Fifteen semi-structured interviews were conducted with purposively selected construction company leaders of large contracting firms in the Western Cape, in positions of Group Chairman, Chief Executive Officer (CEO) or Managing Director in major building construction, civil engineering, or geo-technical companies of good repute. The survey instrument was pretested by construction company leaders before distribution to respondents and the Crobach Alpha test was used in testing the reliability of the study responses. The cidb provided the database of the construction leaders and a survey of contractors listed in Grades 7-9 of the cidb Register of Contractors was conducted. The responses of the samples on the survey question raised on their position also attests to this. At the end of the survey period between April and September 2020, 257 responses were received, representing 56.86% response rate. The data collected were analysed using descriptive and inferential statistics, including Structural Equation Modeling (SEM), to validate the hypothesis developed that construction company leaders positively impact organisational performance through their strategic decisions on project management, change, and innovation and investment. In addition, the study also tested the hypothesis that strategic decisions mediate the relationship between construction companies' leadership components, characteristics, and construction organisation performance. The findings of this study reveal that decisions on change and innovation have the most impact to prevent business failure, and for construction organisation performance. Whilst there are other internal and external factors that may contribute to a firm's business outcomes, the findings of the study explain that the attributes of construction business leaders and their strategic decisions play a significant role in construction company leadership and construction organisation's outcomes. The leadership of construction companies is expected to be exhibit transformational qualities, cast visions, channel new opportunities, and reposition their companies according to the current and future economic situations. The gap between expectations and performance must thus be filled by leadership through their strategic decisions that are premeditated and calculated towards the expectations and visions of the construction companies. The study thus contributes to knowledge in leadership and construction research by demonstrating how the multi-dimensions of company leadership impact construction business organisation performance. The integration of leadership personality traits, skills, style, role, and strategic decisions provides a better measure of how leadership impacts organisational performance. The leadership framework developed from the study's findings made explicit the leadership traits, skills, style and strategic roles that would assist construction company leaders to operate their organisations sustainably and devise effective succession plans. The components of the leadership framework include the strategic leadership roles that construction organisational leaders must play, using catalytic leadership skills, transformational and transactional leadership approaches and inherent leadership traits, which could be developed through education, career experiences, mentoring and training. The study is limited to South Africa, which has implications for the generalisability of results.